Improving Learning Outcomes Through Digital Pop-Up Book Media in Pancasila Education Subjects Cultural Diversity Materials in Grade III of SDS IT Al-Yunusi Rimbo Ulu Tebo - henykurniyawati (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This research is motivated by the low learning outcomes of grade III students in the Pancasila Education subject of cultural diversity material, which is shown by the difficulty of understanding the concept, low activeness, and limited ability to analyze Indonesian cultural information. This condition is influenced by learning that is still dominated by lecture methods and the use of less varied media, so that abstract material has not been understood optimally. This research aims to improve student learning outcomes through the application of digital Pop-Up Book media. The method used is the Kemmis and McTaggart model Class Action Research which is carried out in two cycles, each including planning, implementation of actions, observation, and reflection, with 23 research subjects. Data is collected through observation, tests, and documentation, then analyzed descriptively, qualitatively, and quantitatively. The results of the study showed that the average achievement of students increased from 55 percent in the pre-cycle to 74 percent in the first cycle and 86 percent in the second cycle. Thus, the digital Pop-Up Book media has proven to be effective in improving students' learning outcomes in learning Pancasila Education material on cultural diversity.